Analysis of the Determination of Regional Excellence in the Agricultural Sector in Gorontalo Province - Amir Hamza Hadju; Amir Halid; Ria Indriani (Cita konsultindo, 2024)
This research aims to Analyze the territorial prevalence of agrarian sub-sector in macroeconomic advancement in Gorontalo Province. The results of the study are: Location Quotient (LQ) shows that Food Crops and Fisheries sub-sectors in Gorontalo Province are superior sectors with significant contributions to the local economy. However, other sub-sectors such as Horticulture, Plantation, and Livestock do not have comparative advantage, showing lower contributions compared to the national economy. LQShare and LQShift analyses identify Food Crops as a laggard sector, while Fisheries shows progressive growth potential. The Agricultural Services and Hunting sub-sectors are growing, while other sectors are regressing, indicating challenges in competitiveness and economic development.